Examining the effectiveness of supplementary imaging modalities for breast cancer screening in women with dense breasts: A systematic review and meta-analysis. Issue 154 (September 2022) - Mizzi, Deborah; Allely, Clare; Zarb, Francis; Kelly, Judith; Hogg, Peter; McEntee, Mark; England, Andrew; Mercer, Claire
Highlights: Supplementary imaging to FFDM leads to additional 5.2 per 1, 000 women cancers diagnosed. HHUS resulted in the highest recall and false positive rates when used as supplementary imaging. Randomised Control Trials and longer-term follow-up studies are needed to determine the effectiveness of supplementary imaging modalities. Our analysis shows that evidence on supplementary screening on interval cancers is currently limited. Abstract: Purpose: To systematically review studies on the effectiveness of supplementary imaging for breast cancer screening in women with dense breasts. Materials and methods: A systematic search of peer-reviewed publications in English (January 2000 to March 2021) was carried out. Eight databases were used to retrieve the studies: MEDLINE, CINAHL, Cochrane Central Register of Controlled Trials, Cochrane Clinical Answers, Cochrane Database of Systematic Reviews, Cochrane Methodology Register, PubMed, and Web of Science. Two radiographers and an academic independently reviewed the articles to determine if the studies met inclusion criteria. Study quality was assessed using the Quality Assessment of Diagnostic Accuracy Studies-2 tool. Summary estimates of diagnostic accuracy were obtained by using proportion and diagnostic metanalysis. Results: From 3764 studies that underwent title and abstract screening, 221 studies underwent full-text screening. Of these 42 were included in the qualitative and quantitative synthesis. Results for sensitivity, specificity, positive and negative predictive values, cancer detection rates, recall and biopsy rates in women with dense breasts undergoing supplementary imaging were reported. Studies included in this review were heterogeneous, as was the proportion of women undergoing prevalence and incidence screening rounds. Conclusions: Supplementary screening among women with dense breasts who had recent negative mammograms can consistently identify additional cancers and lead to further recalls and biopsies.